Anemia Prevention Efforts through Health Education and Nutrition Monitoring in Adolescent Girls: A Case Study in Yogyakarta - Neli Fadilatul Masruroh; Ema Waliyanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia is a significant health problem in adolescent girls, caused by increased iron requirements and blood loss during menstruation. This study aims to determine the effect of health education and dietary monitoring through the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) on knowledge and hemoglobin levels in adolescent girls. The research method used is a case study with a pretest-posttest approach on a 12-year-old adolescent girl in Yogyakarta, Yogyakarta. The intervention was carried out in the form of nutritional education and filling out the SQ-FFQ form for three weeks to monitor the consumption of iron and vitamin C sources. The results showed an increase in respondents' knowledge from a score of 70 to 100 after education. In addition, hemoglobin levels increased from 11.1 g/dL to 12.7 g/dL after the intervention of a more varied consumption pattern of iron intake from animal and vegetable protein sources and increased consumption of fruits or vitamin C to support iron absorption, indicating an improvement in respondents' consumption patterns. In conclusion, providing health education accompanied by dietary monitoring is effective in increasing knowledge and improving the hemoglobin status of adolescent girls as an effort to prevent anemia. Keywords: Anemia, Education, Teenagers